Analysis Of Science Learning Process And Its Obstacle In Tugurejo Elementary School 01 Semarang - Azimi, Azimi (Universitas PGRI Palembang, 2019)
The purpose of this research is to analyze the learning process and its obstacle on science subjects in Elementary school. The method used is survey. Activity is done through observation, questionnaire division, and interview. Respondents consisted of 8 teachers and 37 students. Based on the results of the analysis, 75% of teachers like teaching science subjects, 62.5% of teachers use different learning resources, and 87.5% of teachers rarely use instructional media. Judging from the motivation and the spirit of student learning in science lessons, 83.78% of students have motivation and passion in learning, especially learning science and stated very high. Based on the result of research can be concluded that, learning media of IPA and student’s work paper is needed in the learning process. Keywords: Learning Process, Science, Learning Media